Studies on the Synthesis and Characterization, Binding with DNA and Activity of cis-Bisimidazo(1,2-α)pyridinedichloroplatinum(II) - Huq, Fazlul; Abdullah, Ahmed; Chowdhary, Ashraf; Cheng, Howard; Tayyem, Hasan; Beale, Philip (Asian Journal of Chemistry, 2010)
A cis-planaramineplatinum(lI) complex: cis-bisimidazo(1,2-α)pyridine)dichloroplatinum(II) (AH6) has been prepared and characterized based on elemental analyses, IR, Raman, mass and 1H NMR spectral measurements. The interactions of the compounds with salmon sperm and pBR322 plasmid DNAs have been investigated and the activity of the compound against ovarian cancer cell lines: A2780, A2780cis-R and A2780ZD0473R has been determined. The compound is believed to form mainly monofunctional N7(G) and bifunctional intrastrand N7(G)N7(G) adducts with DNA, causing a local distortion of DNA as a result of which gel mobility of the DNA changes. The compound is found to be less active than cisplatin against the three ovarian cancer cell lines. This is believed to be due to its reduced ability to bind with DNA because of a greater steric hindrance introduced by two buIkier planaramine ligands.